2022
DOI: 10.1177/15598276221077224
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Nutrition Counseling into Lifestyle Medicine

Abstract: Despite considerable evidence that plant-based diets can significantly improve health, medical professionals seldom discuss this with their patients. This issue might occur due to minimal training received in medical education, lack of time, and low self-efficacy for counseling patients about diet. Nutrition and lifestyle change should be considered a core competency for all physicians and health professionals looking for cost-effective ways to improve patient health outcomes and reduce nutrition-related chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many patients are aware of this connection and turn to their doctors for advice on nutrition and exercise. However, the nutrition-related components of diseases including cancer, obesity, and diabetes are frequently not adequately addressed in actual physician practice [1]. Doctors may lack enough knowledge of fundamental nutrition science facts and awareness of prospective nutrition interventions if they do not feel competent, at ease, or equipped to offer nutrition advice [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients are aware of this connection and turn to their doctors for advice on nutrition and exercise. However, the nutrition-related components of diseases including cancer, obesity, and diabetes are frequently not adequately addressed in actual physician practice [1]. Doctors may lack enough knowledge of fundamental nutrition science facts and awareness of prospective nutrition interventions if they do not feel competent, at ease, or equipped to offer nutrition advice [2].…”
Section: Introductionmentioning
confidence: 99%
“…The study in India found the effectiveness of a nutrition educational intervention delivered through health services, involving community workers who counseled caregivers regarding the feeding of children (Sharma et al, 2020). Similar to a previous study, the article in the US discusses strategies for health professionals to acquire nutrition counseling skills in medical training and clinical practices (Cepni et al, 2022). Additionally, the study in Ghana observed the nutritional counseling interactions between health workers and caregivers of children under two years, highlighting the role of health workers in providing appropriate nutrition guidance (Nsiah-Asamoah et al, 2019).…”
Section: Resultsmentioning
confidence: 65%
“…Within a clinical setting, patients should be supported in choosing a dietary pattern that fits their needs and preferences. 41,51 Clinicians should allow patients to make informed choices that support them to choose which dietary approach is most suitable for them. At a population level, wider adoption of a culturally appropriate dietary pattern that is higher in plant foods and lower in animal foods can promote health and environmental benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies assessing health benefits of less strict plant-based diets will be necessary to assess these benefits, especially in a study model limiting additional biases (eg, in twins). Within a clinical setting, patients should be supported in choosing a dietary pattern that fits their needs and preferences . Clinicians should allow patients to make informed choices that support them to choose which dietary approach is most suitable for them.…”
Section: Discussionmentioning
confidence: 99%